2023
DOI: 10.1002/eng2.12728
|View full text |Cite
|
Sign up to set email alerts
|

Reducing crosstalk between microstrip lines using CSR structure

Yafei Wang,
Chenlong Li,
Xuehua Li

Abstract: Aiming at the problem of crosstalk between microstrip lines, a method of reducing crosstalk by using cross‐shape resonators (CSR) structures is proposed. On the premise of not changing the spacing of microstrip lines, this method adds CSR structures between the coupled microstrip lines to increase the capacitive coupling and thus to suppress the far‐end crosstalk. Based on the analysis of the equivalent circuit of CSR structure, the parameters simulation and verification are carried out by ADS and HFSS softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The review also presents novel methods for mitigating crosstalk, a major concern in high-speed data transmission. One study introduces Cross-Shaped Resonators (CSR) for microstrip lines, achieving impressive crosstalk reduction without altering line spacing [33]. This simplifies implementation but necessitates further exploration at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The review also presents novel methods for mitigating crosstalk, a major concern in high-speed data transmission. One study introduces Cross-Shaped Resonators (CSR) for microstrip lines, achieving impressive crosstalk reduction without altering line spacing [33]. This simplifies implementation but necessitates further exploration at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the serpentine microstrip layout reduced the near-end (NEXT) and far-end (FEXT) crosstalk by 10 dB and 2 dB, respectively, and showed the best overall crosstalk reduction. Another paper [2] proposes placing a cross-shaped resonator (CSR) structure between the aggressor and victim microstrip lines, which reduces the FEXT crosstalk by up to 15 dB and provides better results than the 3 × W distance rule. A study of microstrips with dielectric coating layers on top is presented in [3]; simulated dielectric layers had thicknesses of up to 7 mil (0.17 mm), and showed a reduction in FEXT crosstalk by up to 24 dB.…”
Section: Introductionmentioning
confidence: 99%